Pharmacokinetics, Disease, and Equipment Related Factors Impacting Intensive Care Unit Patient Outcomes: Comprehensive Review - Praneetha, Aluri; Sathwika, Manchikanti Hima; Rahimunnisa, Shaik; Lokeswari, Perumalla; Dikshitha, Akurathi; Ramya, Sunkara; Krishna, Komaragiri (Indian Journal of Pharmacy Practice)
In unconscious patients, managing treatment presents significant challenges due to the inability to gauge subjective effects and the complexities of altered pharmacokinetics. Critical illness often modifies drug absorption, distribution, metabolism, and excretion, necessitating frequent adjustments in dosing. Additionally, polypharmacy increases the risk of drug interactions, complicating therapy. The absence of patient feedback and the unpredictable nature of drug responses demand meticulous monitoring and individualized treatment plans. Effective management relies on close collaboration among healthcare providers, ongoing therapeutic drug monitoring, and tailored dosing strategies to optimize safety and efficacy. Addressing these issues is crucial for ensuring appropriate and effective drug therapy in this vulnerable population.
Keywords: Communications; Intensive care unit; Metabolism; Pharmacokinetics; polypharmacy; Sepsis